Investigation on the electrical discharge characteristics of a unipolar corona-wire aerosol charger - Intra P. (2014)
In the present study, a simple corona-wire charger for unipolar diffusion charging of aerosol particles is designed, constructed, and characterized. Experimental characterizations of the electrostatic discharge in terms of current-voltage relationships of positive and negative coronas of the corona-wire charger are also presented and discussed. The charging current and ion concentration in the charging zone increased monotonically with corona voltage. The negative corona showed higher current than the positive corona. At the same corona voltages, the current in the discharge zone is about 600 times larger than the charging current. The ion number concentrations ranged within approximately 5.0 × 1010 to 1.24 × 1016 and 4.5 × 1012 to 2 × 1016 ions/m3 in the discharge and charging zones, respectively. A numerical model is used to predict the behavior of the electric potential lines. Numerical results of ion penetration through the inner electrode are in good agreement with the experimental results.